A test of the subsidy–stability hypothesis: the effects of terrestrial carbon in aquatic ecosystems. Issue 6 (1st June 2015) - Jones, Stuart E.; Lennon, Jay T.
Abstract : Global change is altering the movement of materials across landscapes in ways that likely have major consequences for the functioning and stability of ecosystems. For example, the export of dissolved organic carbon (DOC) from terrestrial to aquatic ecosystems is increasing globally. This browning phenomenon is expected to alter the stability of recipient aquatic ecosystems, but theory provides contrasting predictions about the form and direction of this response. We created a gradient in terrestrial DOC supply by adding humic substances on weekly basis to 10 experimental ponds (10 6 L each) over a growing season. The manipulation of terrestrial DOC supply had strong effects on the chemical, physical, and biological properties of the pond ecosystems. Light attenuation linearly increased with terrestrial DOC supply, which created a shading effect that negatively influenced whole‐pond gross primary production and respiration. Despite this, bacterial contributions to basal energy mobilization and respiration increased with terrestrial DOC supply indicating that aquatic food webs were subsidized by terrestrial inputs. After establishing the DOC gradient, we used dynamic linear models to test the subsidy–stability hypothesis by measuring the resilience and sensitivity of each pond to a pulse nutrient perturbation. We found that recovery from the perturbation decreased nonlinearly along a gradient in terrestrial DOC supply. Reciprocal transplant experiments indicated that owing primarily to its light attenuating properties and recalcitrant nature, terrestrial DOC diminished aquatic ecosystem stability by reducing nutrient turnover rates (NTR). Together, our results demonstrate that global‐change‐mediated alterations in the movement of material and energy between habitats can have unpredictable and dramatic impacts on the reliability of ecosystem services.